The impact of watching tv drama series on English learning among university students - Teo, Zhi Enn (2023)
Watching drama has become a daily leisure activity among university students nowadays. Studies showed that there are 54.5% of Malaysian watching drama during their leisure time. During the pandemic, students might have spent more time staying indoor watching drama as an entertainment activity. Plus, there are research showed that watching drama could be an effective learning platform for learning and improve language. Therefore, this research aims to (1) identify the impact of watching TV drama series on English learning among university students and (2) investigate other pedagogical tools used by university students to learn English. This study was conducted in quantitative method by giving out questionnaire-checklist to gather significant data for this study. The data was collected from university students in Klang Valley. The findings of this study showed that respondents’ listening skills, reading ability and their pronunciations has been improved while they are watching English drama series. Besides, the respondents have also use other pedagogical tools to learn English such as RED, Podcast and YouTube.